2013
DOI: 10.3892/ijo.2013.2157
|View full text |Cite
|
Sign up to set email alerts
|

Halofuginone induces the apoptosis of breast cancer cells and inhibits migration via downregulation of matrix metalloproteinase-9

Abstract: Abstract. Halofuginone (HF) is extracted from Dichroa febrifuga, a plant used in traditional medicine. We report that the HF extract inhibits the growth of breast cancer cells and induces the generation of reactive oxygen species (ROS) and apoptosis, an important feature of potential anticancer agents. In addition, HF significantly reduces the migration and invasion of MCF-7 and MDA-MB-231 human breast cancer cells after 12-O-tetraecanoylphorbol-13-acetate (TPA) stimulation. As matrix metalloproteinase-9 plays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 36 publications
1
31
1
Order By: Relevance
“…One recent study demonstrated that halofuginone could reduce tumor growth [31]. However, in our in vivo study halofuginone alone cannot significantly reduce tumor growth, but combination treatment with radiation and halofuginone caused significant inhibition of tumor growth compared to halofuginone or radiation alone.…”
Section: Discussioncontrasting
confidence: 56%
“…One recent study demonstrated that halofuginone could reduce tumor growth [31]. However, in our in vivo study halofuginone alone cannot significantly reduce tumor growth, but combination treatment with radiation and halofuginone caused significant inhibition of tumor growth compared to halofuginone or radiation alone.…”
Section: Discussioncontrasting
confidence: 56%
“…Like all other types of solid tumors, breast cancer is a refractory disease. Although there are tremendous amount of cancer‐fighting drugs, including chemical drugs, which have low efficacy and inherent degree of toxicity, and may result in acquired drug resistance (Jin, Park, Kim, Park, & Lee, ). Therefore, clinicians must perennially to explore new, less toxicity and more effectual therapeutic molecules for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that oroxylin A could inhibit migration and invasion of human breast MDA-MB-435 cancer cells via the inhibition of MMP-2 and MMP-9 (11). Thus, MMP-2 and MMP-9 have been considered as targets in the development of drugs against tumor invasion and metastasis (12,13).…”
Section: Introductionmentioning
confidence: 98%